Pd Nanocatalyst Adorned on Magnetic Chitosan@N-Heterocyclic Carbene: Eco-Compatible Suzuki Cross-Coupling Reaction - Sedghi, Roya; Heidari, Bahareh; Shahmohamadi, Hatef; Zarshenas, Pourya; Varma, Rajender S (Molecules (Basel, Switzerland), 2019)
A novel magnetic-functionalized-multi-walled carbon nanotubes@chitosan N-heterocyclic carbene-palladium (M-f-MWCNTs@chitosan-NHC-Pd) nanocatalyst is developed in two steps. The first step entails the fabrication of a three-component cross-linking of chitosan utilizing the Debus-Radziszewski imidazole approach. The second step comprised the covalent grafting of prepared cross-linked chitosan to the outer walls of magnetically functionalized MWCNTs (M-f-MWCNTs) followed by introducing PdCl2 to generate the m-f-MWCNTs@cross-linked chitosan with a novel NHC ligand. The repeated units of the amino group in the chitosan polymer chain provide the synthesis of several imidazole units which also increase the number of Pd linkers thus leading to higher catalyst efficiency. The evaluation of catalytic activity was examined in the expeditious synthesis of biaryl compounds using the Suzuki cross-coupling reaction of various aryl halides and aryl boronic acids; ensuing results show the general applicability of nanocatalyst with superior conversion reaction yields, high turnover frequencies (TOFs) and turnover numbers (TON). Meanwhile, nanocatalyst showed admirable potential in reusability tests, being recycled for five runs without losing significant activities under optimum reaction conditions. The successfully synthesis of catalyst and its characterization was confirmed using the Fourier transform infrared spectrometer (FT-IR), spectrometer transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray photo-electron spectroscopy (XPS) and thermogravimetric analysis (TGA).
Keywords: MWCNTs; Imidazoles; cross-linked chitosan; Spectroscopy, Fourier Transform Infrared; nanotrubičky uhlíkové; imidazoly; termogravimetrie; N-heterocyclic carbene; methan; Palladium; Methane; Chitosan; palladium; Thermogravimetry; magnetické jevy; chitosan; Magnetic Phenomena; Catalysis; Nanotubes, Carbon; Suzuki cross-coupling reaction; katalýza; spektroskopie infračervená s Fourierovou transformací